Kualitas Air Sungai Pampang di Sekitar TPA Pampang Harapan Kabupaten Kayong Utara Kalimantan Barat - Aripin, Samsun; Gusmayanti, Evi; Fathmawati, Fathmawati (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Pollution in the Pampang River is caused by sand mining and residential domestic waste. The potential for pollution can reduce environmental quality and public health if there is no proper management. Testing for dissolved solids (DSS), pH, chemical oxygen demand (COD), biological oxygen demand (BOD), dissolved oxygen (DO), oil and fat, total coliform bacteria (TCF), and fecal coliform bacteria (FCF) is the goal of this study. January and April 2022 were the months in which the study was conducted. This study used a descriptive and analytical approach, drawing from both primary and secondary sources, and analyzing the results using the STORET technique. Generally speaking, the Pampang River's water state in January 2022 satisfies river water quality criteria. Several measures measuring the quality of river water were found to be over the norms in April 2022. These measurements included COD, BOD, and DO. Class I water quality is moderately contaminated at upstream point A1, according to the study's findings, whereas intermediate and downstream areas A2 and A3 are mildly polluted. Sites A1, A2, and A3 in Class III are somewhat contaminated. Class IV sites A1, A2, and A3 are clean, however. Locations A2 and A3, which are closer to the landfill, often have superior river water quality than A1. This shows that the source of Pampang River water pollution does not only come from the Pampang Harapan landfill, but also comes from community activities such as sand mining and domestic waste from settlements around the river.  Keywords : Pampang river; STORET; water quality